Describtive study to Foliose Lichen Xanthoria parietina From Misurata, Libya - Asma S. Alilesh; Marwa E Elwash; Nawara B. Al-Torjman; Shayma S. El-Hamrush; Doaa Mohammed Al-Dabiba (African Journal of Advanced Pure and Applied Sciences, 2025)
Lichens are a stable lasting symbiotic relationship between mycobiont (fungus) and a photobiont (algae or cyanobacteria). Lichens have great potential in biotechnological applications due to their wide biodiversity, ability to produce bioactive secondary metabolites, and effective capacity to accumulate air depositions. This study aimed to study the foliose lichen associated with the Pinus sp. tree in Misurata. According to the results, Xanthoria parientina was the only and common foliose lichen found on the trunk of the Pinus tree in the studied areas. Collected Xanthoria parientina revealed as a phenotypic variant with a small thallus size (1-1.5 cm). Total soluble protein and chlorophyll contents in the control sample were 1.5 mg/ml and 0.8 µg/mg dry mass, respectively. This preliminary study provides baseline information about this unstudied field to draw the attention of researchers to start local lichenological studies in the east and west of Libya.